Anesthetic management toxemia. - Enciso Nano, Jorge (2015)
The anesthetic management of patients toxemic is a challenge for the  anesthesiologist. The anesthesiologist should play a leading role in the development of delivery of toxemic patient. Because of his experience in pain management, care of the airways and ventilatory care and monitoring of the important effects that both toxemia and its treatment can have the anesthesia, the anesthesiologist should be named in consultation early to take rightful role in the care of these patients. As medical practice is unacceptable to call the anesthesiologist just before delivery to say, "Now is the time to sleep in the patient."